Histórias de empreendedores: significados, narrativas e artefatos - Seloti Junior, Sergio Luis (2015)
This paper aims to understand the process of interpretation and reinterpretation that entrepreneurs attach to new business through the steps: scanning, interpretation and learning, as proposed by Daft and Weick (1984). Design/methodology/approach: From an interpretative perspective, this work made use of qualitative approaches. Narrative Analysis techniques, Antenarrative analysis and qualitative data analysis were made on interviews with 11 digital entrepreneurs at two different moments. Findings: Analyses suggest that entrepreneurs reframes their business over time, probably due to the project's success level. This research supports the proposition of Daft & Weick (1984) about the existence of a cyclical process of search, interpretation and action that would lead to a continuous reinterpretation. Implications: For entrepreneurs (practitioners), this work sheds light on the possibilities of narrative as resources to influence and spread of meanings (sensegiving). For academics, this work offers better conceptualization of the construct 'strategic artifact', and advance the consolidation of narrative analysis methods. Originality/Value: The value of this research takes place on strengthening the narrative analysis methods, and present a possible way to capture and study the ressignification elements. Furthermore, by proposing a framework of analysis and construction of entrepreneurial narrative, this work may help researchers and practioners.